Analisis Pengaruh Program Pendekatan Inovatif Budidaya Sayuran dengan Memanfaatkan Teknologi Smart Farming Berbasis IoT terhadap Efisiensi Produksi Tanaman pada Kelompok Wanita Tani Desa Jatimulyo - Susridar, Susridar; Khasanah, Nur; Waluyo, Bibit (LP3M Universitas Putra Bangsa, 2024)
Farmer groups often face various problems in terms of production activities, one of which is the problem of production efficiency. When a production activity does not run efficiently, it will have an impact on the waste of resources spent. In the end, it will reduce the profits obtained. Therefore, PIKMa Universitas Putra Bangsa proposed the Innovative Approach to Vegetable Cultivation Program by Utilizing IOT-Based Smart Farming Technology in the Jatimulyo Village Women's Farmer Group as a PPK ORMAWA activity to be funded by DIKTI. A program is expected to run effectively to ensure that the budget that has been disbursed by the government is not wasted. Therefore, it is necessary to evaluate the programs that have been carried out in order to see the impact of the program. This study was conducted to see the impact of the Innovative Approach to Vegetable Cultivation Program by Utilizing IOT-Based Smart Farming Technology to Increase the efficiency of vegetable production carried out by the Jatimulyo Village Women's Farmer Group, Alian District. The sample in this study were all members of the Jatimulyo Village women's farmer group, Alian District, Kebumen Regency. The data used in this study are primary data collected and then analyzed using simple linear regression which was previously tested for validity and reliability. Based on the analysis conducted, it is proven that the Innovative Vegetable Cultivation Approach Program by Utilizing IOT-Based Smart Farming Technology has a significant effect on Crop Production Efficiency in the Women Farmers Group of Jatimulyo Village, Alian District.